Gambling attitudes and beliefs associated with problem gambling: the cohort effect of Baby Boomers. Issue 1 (2nd January 2016) - Tanner, Jessica; Mazmanian, Dwight
Abstract: Recreational and problem gamblers alike hold beliefs about gambling that are dysfunctional. These dysfunctional beliefs have been theorized to play a role in problem gambling behaviour. The current study sought to examine the effects of gambling attitudes and beliefs on problem gambling behaviour across three cohorts. A sample of 308 participants consisted of 101 individuals from Generation X, 139 from the Baby Boom cohort and 68 from the Silent Generation. Hierarchical multiple regressions showed that for Baby Boomers, higher scores on scales measuring beliefs about luck and illusions of control were associated with higher scores on measures of problem gambling than for the Silent Generation. Generation X's higher scores on luck scales were associated with higher scores in problem gambling than the Baby Boom cohort. Attitudes associated with problem gambling did not differ among cohorts. These results suggest that while cohorts may not differ in types or levels of distorted beliefs, they differ in how such distortions relate to problem gambling. Future research should focus on determining whether such cohort effects are indicative of differences within the development and maintenance of problem gambling itself.